Electrospinning drug-loaded polycaprolactone/polycaprolactone-gelatin multi-functional bilayer nanofibers composite scaffold for postoperative wound healing of cutaneous squamous cell carcinoma - Yongteng Song; Qingxi Hu; Suihong Liu; Guotai Yao; Haiguang Zhang (Biomedical Technology)
Cutaneous squamous cell carcinoma (cSCC) tumor resection surgery poses challenges due to incomplete cancer cell removal, which increases the risk of local recurrence and micrometastasis, while large-scale surgical wounds are susceptible to severe infections. Therefore, a drug-loaded multi-functional bilayer nanofibers skin scaffold was fabricated for postoperative wound care of cSCC. Briefly, the antibacterial drug enrofloxacin (ENR) was loaded into polycaprolactone (PCL) nanofibers using electrospinning to form an antibacterial nanofiber membrane (PCL-ENR) as the outer layer of scaffold. The anticancer drug bleomycin (BLM) was loaded into PCL/Gelatin (Gel) nanofibers via electrospinning to form an anticancer nanofiber membrane (PG-BLM) as the inner layer of scaffold. ENR and BLM were successfully loaded into the scaffold. The scaffold had excellent physicochemical properties, with the outer layer exhibiting hydrophobicity and excellent antibacterial activity, and the inner layer showing hydrophilicity and outstanding anticancer activity. The elongation at break and tensile modulus of the scaffold were 26.35 ​± ​1.61 ​% and 15.25 ​± ​1.56 ​MPa, respectively. In vitro and in vivo experiments suggested that the scaffold not only has good biocompatibility to promote wound healing but also could inhibit the proliferation of A431 ​cells, which has great potential clinical application in postoperative wound care of cSCC.